Setting the scene for the RTS,S/AS01 malaria vaccine implementation programme in Kenya: a situational analysis of the health system, malaria burden, and immunization platform - Nelli Westercamp; Titus K. Kwambai; Samuel Akech; Simon Kariuki; Philip Bejon; Robert W. Snow; Patricia Njuguna; Meghna Desai; Lucas Otieno; Kibor K. Keitany; Rose Jalang’o; Aaron M. Samuels (Malaria Journal, 2026)
Abstract Kenya has made notable progress in reducing malaria prevalence and improving child survival, yet the lake-endemic region continues to face high transmission and substantial malaria-related illness and death. To strengthen prevention, the RTS,S/AS01 malaria vaccine was introduced in 2019 through Kenya’s Expanded Programme on Immunization (EPI), leveraging a robust platform with decades of experience in rolling out new vaccines. This situational analysis provides a comprehensive description of the demographic, epidemiologic, and health system context in Kenya, with particular attention to the eight high-burden counties where the Malaria Vaccine Implementation Programme (MVIP) was launched. It highlights the organization of the health system, the burden of malaria, ongoing control strategies, and the strength of Kenya’s immunization infrastructure as the backbone for vaccine introduction. By documenting the epidemiologic, health system, and immunization context, this paper provides the foundation for interpreting RTS,S/AS01 malaria vaccine implementation and evaluation findings and offers lessons for vaccine introduction in other malaria-endemic settings.